A worldwide meta-analysis review of restriction criteria for landfill siting using geographic information systems - Fernandez Nascimento, Victor; Loureiro, Anna Isabel Silva [UNESP]; Andrade, Pedro R.; Guasselli, Laurindo Antonio; Ometto, Jean Pierre Balbaud (SAGE Publications, 2021)
One of the most crucial parts of solid waste management is determining landfill site location, since multiple factors must be considered and there is no universal formula. The main purpose of this study is to make a worldwide systematic review of restriction criteria used for landfill siting using geographic information systems (GIS). Literature from the last years was thoroughly assessed, and 45 restrictions found were classified as environmental, economic, or social criteria. Our findings show that although the number of articles published has increased recently, they use on average seven restrictions, focusing mainly on environmental over economic and social criteria. In our boxplot statistical analysis, the most frequently used environmental restrictions are the distance from surface water resources (used in 77% of articles), slope (52%), and distance from groundwater founts (40%), with a median of 300 m, 20%, and 250 m, respectively. The most frequently used economic restrictions are distances from roads (60%), airports (40%), and power lines (18%), with medians of 275 m, 3000 m, and 75 m, respectively. The most frequently used social restrictions are distances from urban areas (45%), settlements and residential areas (40%), and cultural heritage or archaeological areas (23%), with medians of 1000 m. This information might help, on the one hand, governments to develop new legislation about landfill siting and on the other hand, decision-makers and scientists to produce new studies with different restrictive scenarios.
Keywords: economic criteria; Environmental criteria; GIS; social criteria; spatial analysis